2003
DOI: 10.1017/s0305000903005555
|View full text |Cite
|
Sign up to set email alerts
|

Morphosyntactic constructs in the development of spoken and written Hebrew text production

Abstract: This study examined the distribution of two Hebrew nominal structures – N–N compounds and denominal adjectives – in spoken and written texts of two genres produced by 90 native-speaking participants in three age groups: eleven/twelve-year-olds (6th graders), sixteen/seventeen-year-olds (11th graders), and adults. The two constructions are later linguistic acquisitions, part of the profound lexical and syntactic changes that occur in language development during the school years. They are investigated in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…With development, there was an increase in level of abstraction and in the complexity of the syntactic contexts in which such nouns occurred. Ravid & Zilberbuch (2003) found that, with age and schooling, texts became richer in complex nominal structures, in particular written expository texts. A crosslinguistic developmental study in Dutch, English, Hebrew and Spanish texts revealed a consistent increase in complex NPs from childhood to adulthood, again markedly more so in written expository texts.…”
Section: Noun Categories In Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…With development, there was an increase in level of abstraction and in the complexity of the syntactic contexts in which such nouns occurred. Ravid & Zilberbuch (2003) found that, with age and schooling, texts became richer in complex nominal structures, in particular written expository texts. A crosslinguistic developmental study in Dutch, English, Hebrew and Spanish texts revealed a consistent increase in complex NPs from childhood to adulthood, again markedly more so in written expository texts.…”
Section: Noun Categories In Developmentmentioning
confidence: 99%
“…One analysis revealed that NOMINAL DENSITY, which underlies much of the referential and syntactic architecture of texts (Halliday, 1989 ;Biber, 1995 ;Ravid, 2004), increases dramatically in adolescence, towards adulthood. The rich syntactic structure that is typical of adult texts thus consolidates very late in terms of language acquisition, around 16 ; 0 to 18 ; 0, and is highly dependent on the combined effect of literacy and socio-cognitive factors (Nippold, 1998 ;Ravid & Zilberbuch, 2003). Across this study, genre emerges as a stronger diagnostic than modality, a finding which is consistent with results of analyses of other linguistic and discursive features of the same data base in different languages (e.g.…”
Section: S E M a N T I C D E V E L O P M E N T I N T E X T U A L C O mentioning
confidence: 99%
“…Older participants used more than a single noun in the same noun phrase, making it denser and 'heavier', e.g., the Hebrew equivalents of flu shot, hepatitis shot, for the derived noun xisun 'vaccination'. Some derived nouns, like the morphologically related term xósen 'robustness, resistance', seemed to require a heavier noun phrase in order to be used correctly in a sentence, so that all of the adults used this noun as the head of noun compounds or as modified by denominal adjectives in expressions like those meaning 'physical strength', 'economic health', 'mental resistance', and so on [55].…”
Section: Lexicosyntactic Interfacementioning
confidence: 99%
“…One example is use of bound morphology in genitives and compounds where an analytic option is available (e.g., xaveri F ha-xaver sheli 'friend-my = my friend', yaldey ha-kita F hayeladim shel ha-kita 'the children of the class'). A hallmark of high-register written Hebrew [51,55,63], these forms appeared as early as the 6th grade, but with partial and inconsistent use. With age, application of this and other devices for register raising became more consistent and better motivated.…”
Section: Discourse Stance -From Personal To Nonpersonalmentioning
confidence: 99%
“…Against this background, the current study examines the morpho-semantic and syntactic distribution of adjectives in texts produced in speech and in writing by Hebrewspeaking children, adolescents, and adults -in the conviction that the best way to evaluate later-developing linguistic abilities is in the context of extended discourse (Berman, 2008;Ravid & Zilberbuch, 2003). Two dimensions constraining the kind of language used in texts are modality -mode of language production either in speech or in writing -and genre -text type defined by function, social-cultural practices, and communicative purpose (Paltridge, 1997); in this case, narrative versus expository texts.…”
Section: Introductionmentioning
confidence: 99%